Factors Influencing the Ethnocentric Tendencies to Tanzanians Consumers Toward Purchasing Domestic Anti-Malarial Remedies - Kisawike , Blandina (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2022)
The aim of this study was to explore the factors influencing the ethnocentric tendencies to Tanzanian consumers towards purchasing domestic anti-malarial remedies. A case research design was adopted which helped to discover ideas and insights underlying consumers’ evaluation of anti-malarial remedies as far as consumer ethnocentrism was concerned. Purposive sampling was used to select 9 participants in this study. In this study, it was found out that the ethnocentric tendencies of Tanzanian consumers toward purchasing the domestic anti-malarial remedies were influenced by availability, affordability, quality and days of dosage of the anti-malarial remedies. The findings of this study were expected to provide health professional bodies with knowledge about ethnocentric tendencies of Tanzanian consumers towards purchasing domestic anti-malarial remedies. This would help them to boost the standard of the different domestic medical products and hence encourage Tanzanians to value their domestically produced anti-malarial remedies and other home produced products.